Charles Darwin's shorter publications, 1829-1883 - Darwin, Charles 1809-1882 (Cambridge University Press, 2009)
Charles Darwin's words first appeared in print as a student at Christ's College, Cambridge in 1829, and in almost every subsequent year of his life he published essays, articles, letters to editors, or other brief works. These shorter publications contain a wealth of valuable material. They represent an important part of the Darwin visible to the Victorian public, alongside his ever present sense of humour, and reveal an even wider variety of his scientific interests and abilities, which continued to his final days. This book brings together all known shorter publications and printed items Darwin wrote during his lifetime, including his first and his last publications, and the first publication, with A. R. Wallace, of Darwin's theory of evolution by natural selection. With over seventy newly discovered items, the book is fully edited and annotated, and contains original illustrations and a comprehensive bibliography